Debate as an Alternative Technique of Teaching Speaking for the Students - Larasati Larasati (Universitas PGRI Semarang, 2017)
Nowadays, a problem faced in teaching speaking at school is still about the lack of student’s skill in conveying ideas. How teacher dominates the learning also takes part in aggravating the situation of the learning. The effect of that situation is that the students’ speaking skill is undeveloped optimally. This study reveals the existence of an alternative technique that can be applied by Indonesian teacher, which is debate. The method used is a literature review by adopting many studies, then analyzing it based on the application in the learning. According to the analysis result, it can be seen as an alternative in improving students’ speaking skill.